Population growth, saving, interest rates and stagnation: Discussing the Eggertsson-Mehrotra model - Peter Spahn (Research On Money in the Economy (ROME), 2016)
Post Keynesian stagnation theory argues that slower population growth dampens consumption and investment. A New Keynesian OLG model derives an unemployment equilibrium due to a negative natural rate in a three-generations credit contract framework. Besides deleveraging or rising inequality, also a shrinking population is a triggering factor. In all cases, a saving surplus drives real interest rates down. In other OLG settings however, with bonds as stores of value, slower population growth, on the contrary, causes a lack of saving and thus rising rates. Moreover, the recent fall in market interest rates was brought about by monetary factors.
Keywords: E12; E21; E43; J11; 330; overlapping generations; zero lower bound; deflation equilibrium; natural versus market interest rates